QPGx‐CARES: Qatar pharmacogenetics clinical applications and research enhancement strategies - Rania Abdel‐latif; Radja Badji; Shaban Mohammed; Wadha Al‐Muftah; Hamdi Mbarek; Dima Darwish; Duha Assaf; Daoud Al‐Badriyeh; Hazem Elewa; Nahla Afifi; Naseer Ahmad Masoodi; Amr Salah Omar; et al. (Wiley, 2024)
Abstract Pharmacogenetic (PGx)‐informed medication prescription is a cutting‐edge genomic application in contemporary medicine, offering the potential to overcome the conventional "trial‐and‐error" approach in drug prescription. The ability to use an individual's genetic profile to predict drug responses allows for personalized drug and dosage selection, thereby enhancing the safety and efficacy of treatments. However, despite significant scientific and clinical advancements in PGx, its integration into routine healthcare practices remains limited. To address this gap, the Qatar Genome Program (QGP) has embarked on an ambitious initiative known as QPGx‐CARES (Qatar Pharmacogenetics Clinical Applications and Research Enhancement Strategies), which aims to set a roadmap for optimizing PGx research and clinical implementation on a national scale. The goal of QPGx‐CARES initiative is to integrate PGx testing into clinical settings with the aim of improving patient health outcomes. In 2022, QGP initiated several implementation projects in various clinical settings. These projects aimed to evaluate the clinical utility of PGx testing, gather valuable insights into the effective dissemination of PGx data to healthcare professionals and patients, and identify the gaps and the challenges for wider adoption. QPGx‐CARES strategy aimed to integrate evidence‐based PGx findings into clinical practice, focusing on implementing PGx testing for cardiovascular medications, supported by robust scientific evidence. The current initiative sets a precedent for the nationwide implementation of precision medicine across diverse clinical domains.